The price of anarchy in truckload transportation spot markets - Michael Haughton; Borzou Rostami; Shervin Espahbod (EURO Journal on Transportation and Logistics (EJTL), 2022)
A concept of relevance to spot markets for truck-based freight transportation services is the price of anarchy (PoA), which defines the performance inferiority of decentralized market mechanisms for consummating transactions (vis-à-vis centralized mechanisms). To examine this concept in the context of transportation spot markets, this study uses a combination of behavioral experiments and mathematical optimization. The paper's contributions to the research literature for that context involve (1) addressing the case of freight transportation service providers having service requests information spanning multiple periods; (2) analyzing multiple performance measures; (2) accounting for the performance effects of human behavior; and (3) introducing new behavioral experiments as well as novel and effective analytical procedures to tackle truck-to-load assignment problems. Among the paper's most salient findings is that when performance is measured as the market participants' financial outcome, human behavior in buyer-seller interactions could result in a doubling of the PoA.
Keywords: 330; Spot market; Truckload transportation; Optimization; Pricing decisions; Behavior experiments